Handbook of research on social dimensions of semantic technologies and web services - Cruz-Cunha, Maria Manuela, 1964- (Information Science Reference, 2009)
"This book discusses the new technologies of semantic Web, transforming the way we use information and knowledge"--Provided by publisher.